INISIASI MENYUSU DINI DAN FAKTOR DETERMINANNYA PADA ANAK BALITA DI INDONESIA: Analisis Data Sekunder Survei Demografi dan Kesehatan Indonesia Tahun 2007 - Anies Irawati (Persagi, 2010)
Introduction: Breastfeeding initiated within 1 hour after infant birth is important to successfully exclusive breastfeeding and infant health, especially protective infant from infection desease. In Indonesia, information determinant factors of initiated breastmilk within 1 hour after infant birth are rare. Objective: to evaluate determinant factor of initiated breastmilk within 1 hour after infant birth. Methods: Data demography health survey 2007 (DHS 2007) was analyzed using multiple regression logistic. Result: The proportion initiated of breastmilk within 1 hour after infant birth is 45.6% for infant 0-11 months age, and 45.9% infant 12-23 months age. The proportion initiated breastmilk within 1 hour after birth infant in rural area lower than infant in urban area (44.7% and 46.6%). In the urban area, parity is determinant factor of initiated of breastmilk within 1 hour after infant birth controlling sex of infant, birthweight, mother age, work status, education level, and delivery health care and pregnancy health care. In the rural area, pregnancy health care is determinant factor of initiated of breastmilk within 1 hour after infant birth controlling sex of infant, birthweight, mother age, parity, work status, education level, and delivery health care. Conclusion: The proportion of initiated breastmilk within 1 hour after infant birth stilllow. Keywords: initiated breastmillk, parity and pregnancy health care